Optimal Energy Distribution in a Smart Micro-Grid Containing a Combined Electricity with Heat System Based on Fuel Cell and Energy Storage - Yaser Toghani Holari; Mehran Sanjabi; Farhad Zishan; Mehrdad Ahmadi Kamarposhti (Journal of Engineering Research and Reviews)
Abstract- Aim of the study: Today, electrical and thermal loads have become one of integral components of smart micro-grids, along with the combined sources of electricity and heat production. Methods: the optimal distribution of energy in these smart micro-grids is always one of the basic challenges of managers and operators of these micro-grids. Hence, the optimal management of power generation in a residential micro-grids based on heat and electricity generation is discussed. In this hybrid system, a fuel cell is used to generate electricity and heat, and the battery is also used as a source of energy storage. Results: In the adopted method, at each time step, according to the amount of electrical and thermal consumption, the optimal production amount of this hybrid system is used in such a way that the cost of providing the power of the smart residential micro-grids (the cost of electricity and gas consumption) is minimized. In this regard, the variable costs of electricity prices in low-load, mid-load, and peak consumption hours along with the uncertainty of production and consumption are also considered, which have been ignored in previous researches. Conclusion: In this research, an objective function was formed first, and this objective function is composed of different parts such as the costs of fuel cells, batteries, etc. After that, the objective function is optimized using the advanced gravity search optimization algorithm in such a way that the production costs of the fuel cell hybrid system battery, electricity, and gas consumption are minimized. [J Eng Res Rev 2024; 1(3.000): 68-79]